Excel Methods to Design and Validate in Microelectronics (Complementary Metal–Oxide–Semiconductor, CMOS) for Biomedical Instrumentation Application - Graciano Dieck-Assad (MDPI AG, 2021)
CMOS microelectronics design has evolved tremendously during the last two decades. The evolution of CMOS devices to short channel designs where the feature size is below 1000 nm brings a great deal of uncertainty in the way the microelectronics design cycle is completed. After the conceptual idea, developing a thinking model to understand the operation of the device requires a good “ballpark” evaluation of transistor sizes, decision making, and assumptions to fulfill the specifications. This design process has iterations to meet specifications that exceed in number of the available degrees of freedom to maneuver the design. Once the thinking model is developed, the simulation validation follows to test if the design has a good possibility of delivering a successful prototype. If the simulation provides a good match between specifications and results, then the layout is developed. This paper shows a useful open science strategy, using the Excel software, to develop CMOS microelectronics hand calculations to verify a design, before performing the computer simulation and layout of CMOS analog integrated circuits. The full methodology is described to develop designs of passive components, as well as CMOS amplifiers. The methods are used in teaching CMOS microelectronics to students of electronic engineering with industrial partner participation. This paper describes an exhaustive example of a low-voltage operational transconductance amplifier (OTA) design which is used to design an instrumentation amplifier. Finally, a test is performed using this instrumentation amplifier to implement a front-end signal conditioning device for CMOS-MEMS biomedical applications.